Associations between COVID-19 Vaccination Hesitancy, Related Barriers and Some Sociodemographic Factors in Duhok City, Iraq - Sultan Muhamad Mizuri, Sarwin; Salih Ibrahim, Dler (Al-Nahrain Journal of Science, 2025)
The most crucial public health achievement of humanity is vaccination. Conversely, a significant portion of the population remains hesitant regarding vaccines. The purpose of the study is to determine the prevalence and the reasons that affect the rate of vaccination against COVID-19, which is caused by virus named SARS-CoV-2, in Duhok City. A cross-sectional survey was conducted online from (November to January 2022), about 2015 participants were enrolled. The data were collected through a designated online questionnaire using Google Forms. The study results showed that females were more accessible to the vaccine (50.8%) than males (44.5%). More than half of the participants (n= 1147, 56.9%) were aged between 20–29 years. The majority of participants were from Duhok (n= 799, 39.7%), followed by Zakho (n= 691, 34.3%), and fewer from Bardarash (n= 30, 1.5%). Moreover, the study revealed that the acceptance of the vaccine was more associated with young people, female gender, those with high educational levels, healthcare workers, and residents of Batifa district. To conclude, more than half of enrolled research individuals rejected to have the vaccine for COVID-19, Thus, we recommend integrating health and psychological care into vaccination plans to help increase the uptake rate during potential subsequent pandemics. Also, Psychologists can provide awareness messages, counselling seminars, online mentoring, or telemental health outreach. Furthermore, Governments must progress announcements also raising confidence concerning to health problems through the dispersion of scientific culture and improve educational programs in society.